How Relevant Is Occlusion of Associated Developmental Venous Anomaly in Cerebral Cavernoma Surgery? A Clinical and Radiographic Comparison Study - Tantongtip, Dilok; Spetzger, Uwe; Arnold, Sebastian; von Schilling, Andrej; Kiriyanthan, George (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Background A developmental venous anomaly (DVA) associated with cerebral cavernous malformation (CCM) is the most common combined vascular malformation. Microsurgical resection of the CCM and avoidance of damage to the adjacent DVA is an overall accepted treatment regimen. Several publications have demonstrated serious consequences that possibly occur after damage of the associated DVA. Conversely, some authors have reported cases of injured DVAs without any relevant postoperative complications. This study compared the clinical and radiologic outcome in patients with and without occlusion of an associated DVA, following microsurgical removal of intracerebral cavernomas.Methods In this single-center evaluation, all consecutive CCM surgical patients from January 1, 2006, to December 31, 2011, were reviewed in a retrospective cohort study. Follow-up was from 12 months to 7 years. The patients were divided into three groups: group I, CCM without associated DVA; group II, damage and occlusion of the associated DVA during CCM removal; and group III, preservation of the associated DVA following CCM removal. Preservation and damage, respectively, of the DVA were defined by evaluation of the corresponding pre- and postoperative magnetic resonance (MR) image sequences. The clinical and radiographic findings in all three groups were evaluated and compared.Results A total of 38 patients underwent microsurgical resection of a CCM. Overall, 24 patients (63%) had no associated DVA (group I), in 10 patients (26%) the associated DVA was impaired and occluded (group II), and in 4 patients (11%) the associated DVA was surgically not impaired and confirmed as preserved (group III). The rate of postoperative neurologic deficits was 37.5% in group I, 10% in group II, and 75% in group III (p = 0.05). Subgroup analysis in patients with preserved DVA (group III) showed a higher incidence of new postoperative neurologic deficits than in patients with impaired DVA (group II) (p = 0.041). However, no significant difference was seen in patients with no associated DVA (group I) and patients with impaired DVA (group II) (p =0.215). The average postoperative Karnofsky score was 88.33 ± 9.17 in group I, 92.0 ± 6.32 in group II,; and 90.0 ± 8.16 in group III (p =0.51). The peri-resectional edema volume in group I was 8.90 ± 9.75 cm3; in group II, 8.16 ± 3.78 cm3; and in group III, 2.48 ± 1.48 cm3 (p = 0.35). The location (eloquent or noneloquent region) of the CCM and the DVA, respectively, was the only significant factor for any additional neurologic deficit (p = 0.001).Conclusion Our results demonstrated similar postoperative clinical outcomes and radiographic findings between patients with impaired and unimpaired DVA after resection of CCMs. Postoperative MR images showed less peri-resectional edema in patients with preserved and unimpaired DVA. However, these results will not convert the paradigm in cavernoma surgery to preserve the associated DVA. The overall goal is still preservation of unimpaired venous drainage, but our results show that the occlusion of a DVA adjacent to a CCM can be tolerated because of a low risk of complications.
Keywords: cavernoma; developmental venous anomaly; DVA injury